Development of a magnetic activated carbon adsorbent for the removal of common pharmaceuticals in wastewater treatment - Vargues, F. (2021)
This work aims to study the use of a powdered activated carbon with magnetic properties as adsorbent to remove common pharmaceuticals in wastewater treatment. This hybrid material was prepared from powdered activated carbon that was combined with iron oxide nanoparticles and was characterized by infrared spectroscopy and X-ray diffractometry. It was also assessed for its adsorption ability using ibuprofen and amoxicillin as model drugs. Under the tested conditions, adsorption equilibrium was reached at 160 min for both drugs, with removal rates of 95% for the former and 90% for the latter. Adsorption data were fit to several adsorption kinetics and isotherm models. the adsorption of ibuprofen seems to follow a pseudo-order n kinetics and fits best the Redlich-Peterson isotherm model, whilst that of amoxicillin shows best fits to the Bangham kinetics and Temkin isotherm models. the new adsorbent also proved to be efficient in an urban wastewater spiked with both drugs and to keep its adsorption ability upon regeneration by desorption.